Ultraviolet index: a light in atopic dermatitis and vitamin D research? - Kleyton de Carvalho Mesquita; Ana Carolina de Souza Machado Igreja; Izelda Maria Carvalho Costa (Sociedade Brasileira de Dermatologia, 2016)
Abstract BACKGROUND: The role played by vitamin D in atopic dermatitis is controversial and has been the focus of many studies. The ultraviolet index has not been considered in this type of research. OBJECTIVES: The objectives of the study were to assess 25-hydroxy vitamin D [25(OH)D] serum level in atopic dermatitis patients and control group, to investigate the association between atopic dermatitis clinical severity (using the SCORing Atopic Dermatitis index - SCORAD) and 25(OH)D serum levels, and to evaluate the independent predictors, including Ultraviolet index, SCORAD and 25(OH)D. METHODS: We conducted a cross-sectional study of 106 atopic dermatitis patients. A control group was matched with a subsample of 54 participants with atopic dermatitis. SCORAD index, laboratory tests, and local Ultraviolet index were assessed. RESULTS: The atopic dermatitis patients had serum 25(OH)D levels and mean UVI significantly higher than the control group. Immunoglobulin E and Ultraviolet index were associated with the SCORAD index. Skin type, age and Ultraviolet index were independent predictors of 25(OH)D. CONCLUSIONS: Although statistically significant, the different levels of 25(OH)D between the paired groups may be attributed to the higher mean Ultraviolet index in atopic dermatitis patients. Since Ultraviolet index is an independent predictor of SCORAD index and of 25(OH)D level, it may work as a confounding factor in studies involving atopic dermatitis and 25(OH)D and must be considered in this kind of research.